TEACHERS’ CHALLENGES IN ENGLISH CLASSROOM MANAGEMENT AT MAS DARUSSALAM ANRONG APPAKA PANGKEP - Syahruni, Syahruni; Weda, Sukardi; La Sunra, La Sunra (State University of Makassar, 2022)
Classroom management is needed in every teaching and learning process, including the English teaching and learning process. This study aims to find out the English teachers’ challenges in English classroom management at MAS Darussalam Anrong Appaka Pangkep and to describe the strategies used by the teacher to cope with the challenges in English classroom management at MAS Darussalam Anrong Appaka Pangkep. This study is descriptive qualitative research. The subjects of this research are three English teachers. The data were collected through observation and interview. The results of the research showed the teachers got challenge in English classroom management at MAS Darussalam Anrong Appaka Pangkep. Based on the observation and interview it was found that the challenges they faced were linguistic challenges, psychological challenges, institutional challenges, and instructional challenges. Based on these findings, the researcher concluded three factors of linguistic challenges: the students' lack of vocabulary, pronunciation, and lack of understanding of the grammatical pattern. The researcher also found some psychological problems: lack of motivation, lack of confidence, and students’ fear of making mistakes. Furthermore, the results also indicate that there were strategies used by the teachers to cope with the challenges in English classroom management at MAS Darussalam Anrong Appaka Pangkep. The strategies were related to determination strategy, group discussion strategy and communication strategy. Keywords: Classroom Management, teachers’ challenges, teachers’ strategies